2017
DOI: 10.3389/fnins.2017.00643
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Antipsychotic Drug-Induced Diabetes

Abstract: Antipsychotic drugs (APDs) are widely prescribed to control various mental disorders. As mental disorders are chronic diseases, these drugs are often used over a life-time. However, APDs can cause serious glucometabolic side-effects including type 2 diabetes and hyperglycaemic emergency, leading to medication non-compliance. At present, there is no effective approach to overcome these side-effects. Understanding the mechanisms for APD-induced diabetes should be helpful in prevention and treatment of these side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 144 publications
2
53
0
1
Order By: Relevance
“…Smoking, obesity, and lower SES were associated with antipsychotic use also in our material. Use of S-GAs can affect normal glucose metabolism and induce weight gain by inhibiting the insulin signaling pathway which leads to insulin resistance and increased insulin production, or by direct damage to pancreatic beta cells [29]. During pregnancy, high maternal blood glucose results in increased fetal insulin production.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking, obesity, and lower SES were associated with antipsychotic use also in our material. Use of S-GAs can affect normal glucose metabolism and induce weight gain by inhibiting the insulin signaling pathway which leads to insulin resistance and increased insulin production, or by direct damage to pancreatic beta cells [29]. During pregnancy, high maternal blood glucose results in increased fetal insulin production.…”
Section: Discussionmentioning
confidence: 99%
“…Muscarinic M 3 receptor was an important receptor involved in antipsychotic‐induced diabetes, blockade of which on pancreatic β‐cells might decrease insulin secretion . As a matter of fact, olanzapine and clozapine with highest potency for M 3 receptor among antipsychotics had the highest risk to induce diabetes .…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic disorders such as weight gain, insulin resistance and diabetes are common and serious side-effects of antipsychotics, especially for atypical antipsychotic drugs [6,8]. A recent meta-analysis in 25 studies with 154,718 schizophrenia and 4,343,407 control subjects showed antipsychotic treatment led to 2.5 times higher risk of type 2 diabetes (T2D) [33].…”
Section: Bdnf Val66met Polymorphism and Metabolic Disordersmentioning
confidence: 99%